Penerapan Pengungkapan Sustainability Reporting Terhadap Kinerja Keuangan Perusahaan - Dewi Zakia; Endah Yuni Puspitasari; Lihan Rini Puspo Wijaya; Sahilly Dzulhasni (Politeknik Negeri Lampung, 2023)
This study aims to examine the effect of information value in terms of financial statement disclosure as measured using the GRI index and divide it into two main categories, namely hard environmental disclosure and soft environmental disclosure and sustainability reporting on company stock prices. The research was conducted on ISRA participants in 2020-2022. The company's stock price is measured using the price model developed by Ohlson (1995). Data were analyzed using multiple linear analysis.